PENGARUH RISIKO BISNIS, ASET COLLATERAL DAN INVESTMENT OPPORTUNITY TERHADAP KEBIJAKAN DIVIDEN DENGAN CASH POSITION SEBAGAI VARIABEL MODERASI - Catur Ragil Sutrisno; Irvina Refiyanti (Journal of Accounting and Finance, 2026)
This research aims to test and analyze the effect of business risk, collateral assets and investment opportunities on dividend policy with cash position as a moderating variable. The population in this research are consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange in 2019-2023. Based on the purposive sampling method, the sample obtained was 140 samples from 28 consumer non-cyclicals sector companies that met the research criteria. The hypothesis testing used in this study is moderation regression analysis. The results of the study indicate that business risk and investment opportunities have a positive effect on dividend policy, collateral assets do not affect dividend policy, cash position weakens the effect of business risk on dividend policy, cash position does not moderate the effect of collateral assets on dividend policy and cash position does not moderate the effect of investment opportunities on dividend policy.